DIPLOMASI PUBLIK INDONESIA DALAM MENJADIKAN KARIMUNJAWA SEBAGAI CAGAR BIOSFER UNESCO - Alzura, Intan; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Karimunjawa is a tourism area which is famous for its lowland tropical rain forests, mangrove forests, coastal forest ecosystems, sea grass ecosystems, coral reefs with the specifications of coral reefs reaching 7,487.55 hectares, and the types of mangroves in Karimunjawa are mostly classified as true mangroves. which attracts many people from abroad. This fact shows that the natural wealth and attractiveness of Karimunjawa is not inferior to the Indonesian region which is recognized by the international community. However, Karimunjawa has not been registered and recognized globally. For this reason, the Ministry of Environment and Forestry of Jepara, Karimunjawa Islands was submitted to UNESCO to be included in UNESCO World Biosphere Reserves in 2017 through the Public Diplomacy strategy with the aim that the Karimunjawa Islands get international protection. The author uses a qualitative method with a case study research approach. Primary data is based on data collection from official government agencies involved including the Jepara tourism office and the Ministry of Environment. The primary data will be supported by secondary data derived from data from UNESCO, literature, journals or trusted websites related to the government's efforts to make Karimunjawa a UNESCO World Biosphere Reserve through public diplomacy. This study uses the Mark Leonard's Diplomacy theory at the level of analysis of the Nation-State. Through public diplomatic strategies news management, strategic communication, and the relationship building karimmunjava are selected because of the unique ecosystem between islands, lowlands, and mountains that make up part of the 714 UNESCO's largest UNESCO version of the world's biosphere reserve in 129 countries. In the 32-international council (ICC) man and the biosphere (mab) October 28, 2020. Key words: UNESCO, karimmunjava, biosphere reserve, public diplomacy